1984
DOI: 10.1111/j.1365-2265.1984.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

A Receptor Assay for the Measurement of TSH Receptor Antibodies in Unextracted Serum

Abstract: A receptor assay for TSH receptor antibodies is described in which unextracted serum, detergent solubilised TSH receptors and 125I-labelled TSH are used. The assay was rapid and reproducible with coefficients of inter-assay variation of 12.3%, 2.1 and 2.6% at mean inhibition of TSH binding values of 11, 53, and 79 respectively. Assay sensitivity could be increased by reducing the volume of receptors used but some increase in the scatter of values obtained with individual normal sera was also observed. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
3

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(82 citation statements)
references
References 12 publications
3
76
0
3
Order By: Relevance
“…In this method, 125 I-labeled bovine TSH compete with TRAb in serum samples to bind to purified porcine TSH receptors, followed by polyethylene glycol precipitation (13). After the completion of our study, new generations of TRAb assays have been developed (14,15), and it has been shown that a minor subset of sera from patients with Graves' disease are falsely negative using the assay employed in our study (15).…”
Section: Methodsmentioning
confidence: 99%
“…In this method, 125 I-labeled bovine TSH compete with TRAb in serum samples to bind to purified porcine TSH receptors, followed by polyethylene glycol precipitation (13). After the completion of our study, new generations of TRAb assays have been developed (14,15), and it has been shown that a minor subset of sera from patients with Graves' disease are falsely negative using the assay employed in our study (15).…”
Section: Methodsmentioning
confidence: 99%
“…Most related studies have been performed using the first-generation TBII assay and yet second-generation assays are nowadays widely available. Instead of solubilized porcine receptors (14,15), these newer assays use recombinant TSHR coated on a solid-phase surface which provides a markedly improved sensitivity and specificity (16,17,18). To our knowledge, the threshold value indicating a risk for fetal or neonatal autoimmune hyperthyroidism with a second-generation TBII assay has only been investigated in one small study (19).…”
Section: Introductionmentioning
confidence: 99%
“…TSH binding inhibition assays were carried out according to the method of Southgate et al (1984) using native human TSHR or recombinant human TSHR (expressed in CHO cells). Briefly, 50 µl detergent solubilised TSHR were preincubated with 50 µl sera, purified IgG or Fab fragment for 15 min at room temperature before the addition of 100 µl 125 I-TSH (30 000 c.p.m.)…”
Section: Tsh Binding Inhibition Assaysmentioning
confidence: 99%